The apothecary diaries. Volume 9 - Hyūga, Natsu (Square Enix Manga & Books, a division of Square Enix, Inc., 2023)
"A festive atmosphere descends upon the Inner Court with the arrival of a long-awaited merchant caravan and its myriad wares. Though the excitement is contagious and even Maomao looks forward to making purchases of her own, she soon cottons on to something potentially sinister about the innocuous goods for sale. Before Maomao can tease out any evidence, however, her attention turns to mushrooms when Jinshi asks her to root out any poisonous varieties on the grounds. But is this request just a bit of landscaping or does it have anything to do with the rumors making the rounds about a court lady who has gone missing?"--Provided by publisher